The association between female genital fistula symptoms and gender-based violence - Tripathi, Vandana; Mallick, Lindsay (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: This study examined the association between self-reported female genital fistula symptoms and experience of gender-based violence (GBV) among women interviewed in Demographic and Health Surveys (DHS) surveys. Methods: This study pooled data from 13 recent DHS surveys with both fistula and domestic violence modules. Multivariable logistic regressions controlled for maternal and demographic factors. Results: In this sample of 95,625 women, the prevalence of self-reported fistula symptoms ranges from 0.3% to 1.8% across countries. Among women reporting fistula symptoms,56% report past experience physical violence, more than among women with no symptoms (38%). Twice as many women with fistula symptoms report either lifetime (27%) or recent (16%) experience sexual violence than women not reporting symptoms (13% and 8%, respectively). Women whose first experience of sexual violence was from a non-partner have almost four times the odds of reporting fistula symptoms compared with those who never experienced sexual violence. Conclusions: These findings must be interpreted with caution given the inability to identify temporal and causal relationships through DHS data. However, the increased risk of violence among women with fistula symptoms suggests that fistula treatment programs should incorporate GBV screening, referral, and services into their pre-discharge care.